AJAKAN KEPADA JEMAAT GEREJA PRESBITERIAN INDONESIA (GPI) JEMAAT SINAI GRAHA CITRA TANGERANG, KECAMATAN LEGOK, UNTUK “MENGUCAP SYUKUR” DI TENGAH-TENGAH PANDEMI COVID-19 - Adi Putra; Yunus Selan; Sri Dwi Harti (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
Abstract The Covid-19 pandemic has resulted in systemic hardships and covers almost all aspects of life, including the church members at the GPI Congregation Sinai Ghara Citra Tangerang. That is why through PkM. This and by using the lecture method, we convey and invite church members how they should be grateful even in the midst of difficulties. As a result, the church members responded positively and the materials presented were very blessing for them. Keywords: Giving thanks, Covid-19, Church members